Novel Technologies and Techniques for Prehospital Airway Management: An NAEMSP Position Statement and Resource Document. (4th January 2022) - Counts, Catherine R.; Benoit, Justin L.; McClelland, Graham; DuCanto, James; Weekes, Lauren; Latimer, Andrew; Hagahmed, Mohamed; Guyette, Francis X.
Abstract: Novel technologies and techniques can influence airway management execution as well as procedural and clinical outcomes. While conventional wisdom underscores the need for rigorous scientific data as a foundation before implementation, high-quality supporting evidence is frequently not available for the prehospital setting. Therefore, implementation decisions are often based upon preliminary or evolving data, or pragmatic information from clinical use. When considering novel technologies and techniques. NAEMSP recommends: Prior to implementing a novel technology or technique, a thorough assessment using the best available scientific data should be conducted on the technical details of the novel approach, as well as the potential effects on operations and outcomes. The decision and degree of effort to adopt, implement, and monitor a novel technology or technique in the prehospital setting will vary by the quality of the best available scientific and clinical information: Routine use – Technologies and techniques with ample observational but limited or no interventional clinical trial data, or with strong supporting in-hospital data. These techniques may be reasonably adopted in the prehospital setting. This includes video laryngoscopy and bougie-assisted intubation. Limited use – Technologies and techniques with ample pragmatic clinical use information but limited supporting scientific data. These techniques may be considered in the prehospital setting. This includes suction-assisted laryngoscopy and airway decontamination and cognitive aids. Rare use – Technologies and techniques with minimal clinical use information. Use of these techniques should be limited in the prehospital setting until evidence exists from more stable clinical environments. This includes intubation boxes. The use of novel technologies and techniques must be accompanied by systematic collection and assessment of data for the purposes of quality improvement, including linkages to patient clinical outcomes. EMS leaders should clearly identify the pathways needed to generate high-quality supporting scientific evidence for novel technologies and techniques.